Pengaruh Pertumbuhan Ekonomi, Investasi, dan Belanja Modal terhadap Kesejahteraan Masyarakat di Jawa Tengah Tahun 2012 – 2018 - An Nisa An Nisa; Herniwati Retno Handayani (Diponegoro Journal of Economics, 2021)
Social walfare is one of the main goal of developing area to achieve a better life. The improvement of social walfare can't be separated from economic activities that is done by all kinds of society, from private area and government area. The purpose of this study was to examine the effect of economic growth, domestic investment, foreign investment, and capital expenditure on social walfare at 2012-2018 in Central Java Province. This  study  uses  secondary  data  with  cross-section  data  depends  on  29 districts and 6 cities in Central Java Province and time-series data from 2012- 2018. The analytical tool used in estimating the research model is panel data regression with Fixed Effect Model. The result  study  is  simultaneously, independent  variable has  an  effect  to dependent variable. Meanwhile partially, the variable of domestic investment and capital expenditure have significant effect to social welfare while economic growth and foreign investment have no significant effect to the social walfare in Central Java Province.